Efektivitas Rebusan Biji Ketumbar Dan Rebusan Daun Sirsak Terhadap Penyembuhan Luka Perineum Pada Ibu Postpartum Di Puskesmas Maja, Kabupaten Lebak, Banten - Martini, Martini; Galaupa, Resi (Jurnal Keperawatan Muhammadiyah, 2024)
Background: According to WHO in 2020, almost 90% of normal births experience perineal tears. Based on data from the Maja Health Center, Lebak Banten Regency, in 2022 the number of normal deliveries was 354 people, 178 of whom had grade I and II perineal tears, 1 mother had grade IV perineal tears and 1 of them had an open wound case on the 3rd day postpartum. One solution for postpartum mothers is to use boiled coriander seeds and soursop leaves.Writing Objective: To determine the effectiveness of coriander seed decoction and soursop leaf decoction for perineal wound healing in postpartum women at the Maja Community Health Center, Lebak Regency, Banten.Research Method : Quasy Experiment with post-test only control group design method. The samples were postpartum women with perineal wounds in May-June 2023 who gave birth at the Sukatani Health Center, Bekasi Regency, with a total of 34 samples using a purposive sampling technique. The intervention was given for 10 minutes 2 times a day in the morning and evening after bathing starting on the 2nd day until the 9th day post partum. The researchers measured perineal wound healing using the REEDA Scale with a value of 0-15. Bivariate analysis using independent t-test.Research Results: The average perineal wound healing in postpartum women after giving coriander seed decoction was 2.41 and the average perineal wound healing in postpartum women after giving soursop leaf decoction was 7.18. The results of the independent t-test obtained a p value = 0.000.Conclusions and Suggestions: There is the effectiveness of coriander seed decoction and soursop leaf decoction for healing perineal wounds in postpartum mothers. Postpartum mothers who experience perineal wounds are expected to be able to carry out non-pharmacological treatment in accelerating the healing process of perineal wounds, including using coriander seed decoction or soursop leaf decoction. Besides being cheap, these materials are also available around the yard. In addition, it is expected that postpartum mothers pay attention to personal hygiene and physical activity so as not to overdo it because it affects the healing of perineal wounds.